A revision of Rhombuniopsis Haas, 1920 (Unionida, Unionidae) endemic to the ancient lakes of Yunnan, China, with descriptions of two new species - Xiang, Hong Quan; He, Yue Ming; Zhang, Le Jia; Gao, Han; Guo, Liang; Lu, Yi Zhi; Fan, Shu Yun; Chen, Hui (Zootaxa, 2024)
Freshwater mussels are an important component of the macrobenthic fauna but due to modern environmental pollution and destruction, the abundance of freshwater mussels has declined rapidly, and this fauna is one of the most threatened animal groups in the world. China is the country with the second highest diversity of freshwater mussels in the world. Rhombuniopsis is a genus of freshwater mussels endemic to the ancient lakes and surrounding area in Yunnan Province, China. Species in this genus are threatened with extinction and have not been recorded alive for many years. We present a revision of Rhombuniopsis based on the morphological study of the museum materials and newly collected specimens, and propose two species new to science: Rhombuniopsis linan sp. nov. and Rhombuniopsis songmeng sp. nov. The two new species are considered extinct because the lakes they inhabited were completely dried up due to human activity. We compare our recent data with the historical studies to trace the population change of the Rhombuniopsis species in different lakes. We revise the distribution and assess the conservation status for each species. The present work confirms the importance of conservation of molluscs in the ancient lakes of Yunnan and suggest that several species are already extinct.